Effectiveness of Video Assisted Teaching Program on Prevention of Oral Cancer among Tobacco Chewers in Selected Village of Rupandehi, Nepal - Pokharel, Astha Sharma; Rana, Ikshaya; Shrestha, Pragya; Shrestha, Neelam (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Cancer is defined as the uncontrollable growth of cells that invade and cause damage to surrounding tissue. Oral diseases and conditions share modifiable risk factors with the leading NCDs (Cardiovascular diseases, cancer, chronic respiratory diseases and diabetes). This study was carried out to assess the knowledge regarding prevention of oral cancer and to find out the effectiveness of video assisted teaching program among tobacco chewers. MATERIAL AND METHODS A pre-experimental one group pre-test post-test design study was conducted to find the effectiveness of video assisted teaching for prevention of oral cancer among tobacco chewers in Dhakdahi village of Rohini rural municipality of Rupandehi District, Nepal. The total duration of the study was three months 5/5/2019 to 26/8/2019. The study samples tobacco chewers were selected by non-probability convenient sampling. Self-administered structured questionnaire was used for socio-demographic variables and video in local language for prevention of oral cancer was used as a intervention for the study group and collected data was used analysed by using descriptive and inferential statistics with SPSS software version 20.0 RESULTS The findings of the study show that the mean score pre-test knowledge was 7.23 and standard deviation 1.801. After the intervention, the mean score of post-test knowledge was 9.96 and standard deviation 1.56. No significant association was found between socio -demographic variables and post-test knowledge level. CONCLUSION Based on the study findings the knowledge level on prevention of cancer is inadequate before intervention of video assisted teaching and after the video assisted teaching the knowledge on prevention was found to be improved. There was overall gain in the knowledge score teaching program following the video assisted teaching program.